A Mink, a Fink, a Skating Rink : What is a Noun? - Cleary, Brian P. 1959-; Prosmitsky, Jenya 1974- (Minneapolis : Carolrhoda Books, 1999)
Rhyming text and illustrations of comical cats present numerous examples of nouns, from "gown" and "crown" to "boat", "coat", and "clown."
"Ages 7-9, gr. 2-4"--Jkt.
Keywords: English language -- Parts of speech